DISCIPLINE SCHOOL’S INFLUENCE TO DO NOT BRING CAM HANDPHONE TOWARDS FRESHMENT LEARNS OF STUDENT IN JUNIOR HIGH SCHOOL 7 AT KOTABUMI - Alex Lendro Juniarto Alex Lendro Juniarto; Dr.Adelina Hasyim, M.Pd. Dr. Adelina Hasyim, M.Pd.; Drs. Julyaden Abdul Hay Drs. Julyaden Abdul Hay (FKIP Unila, 2012)
DISCIPLINE SCHOOL’S INFLUENCE TO DO NOT BRING CAM HANDPHONE TOWARDS FRESHMENT LEARNS OF STUDENT IN JUNIOR HIGH SCHOOL 7 AT KOTABUMI Alex Lendro Juniarto, Adelina Hasyim, Zulyaden Abdulhay ABSTRACT The aimed of this research was to explain how the influence of upright discipline school to do not bring cam handphone toward freshmen learns of student class VII-VIII in Junior High School 7 at Kotabumi on 2011/2012. Method used descriptive method with sample as many as 35 respondents. The main data collecting technique used inquiry. Based on data analyses got result that there upright discipline school to do not bring cam handphone toward freshmen learns of student class VII-VIII in Junior High School 7 at Kotabumi. It proved by Chi Quadrate formulation x2 account was higher than x2 table (x2 account ≥ x2 table) as big as 15,96 ≥ 9,94. Then did comparison between C and Cmax, with result 0,69 and it belonged to high categories based on Sugiyono. Key Word: Influence, Discipline, Handphone, Freshmen Learn.